Hepatocyte growth factor (HGF) in patients with hepatitis B and meningitis - Ozden, M; Kalkan, A; Demirdag, K; Denk, A; Kilic, SS (W B Saunders Co Ltd, 2004)
Objectives. The present study investigates serum hepatocyte growth factor (HGF) levels in patients with acute and chronic hepatitis B and the relation between these Levels and intrahepatic inflammatory markers of the liver and fibrosis, as well as the cerebrospinal fluid (CSF) HGF levels in patients with meningitis and the relation between these levels and CSF findings. To our knowledge this is the first study regarding CSF HGF levels in tuberculous meningitis. Patients and methods. The study consisted of 35 patients with chronic hepatitis B (HbeAg and HBV-DNA positive), 20 with acute hepatitis B, 20 with acute bacterial meningitis and 15 having tuberculous meningitis. HGF levels in the serum and CSF samples were measured by using the ELISA method. Results. The mean serum HGF levels in acute hepatitis B group were found statistically significantly higher than those in the control group and chronic hepatitis B group (p < 0.0001). It was established that serum HGF levels in patients with chronic hepatitis B were significantly correlated with serum alanine aminotransferase (ALT) and HBV-DNA levels (r: 0.816, 0.951; p < 0.05, respectively). Similarly, serum HGF levels of patients with chronic hepatitis B were correlated with fibrosis score and hepatic activity index of the liver histopathology (r: 0.750, 0.459; p < 0.05, respectively). The mean CSF HGF Levels of patients with acute bacterial meningitis and tuberculous meningitis were higher than those in the control group (p < 0.05). In addition, it was observed that mean CSF HGF levels in patients suffered from tuberculous meningitis were statistically significantly higher than those in acute bacterial meningitis (p < 0.05). Conclusions. We suggest that serum HGF level in patients with chronic hepatitis B might reflect viral load, necro-inflammatory activity in the liver and the degree of structural progression. Our findings have demonstrated that tuberculous meningitis cause increased HGF concentrations in CSF. It is, therefore, suggested that examination of HGF levels in CSF may provide additional information in the differential diagnosis. (C) 2003 The British Infection Society. Published by Elsevier Ltd. All rights reserved.
Keywords: hepatocyte growth factor; chronic hepatitis B; meningitis; tuberculosis; cerebrospinal fluid; ELISA